Deposition, removal and production site of the amorphous mating plug in the spider Philodromus cespitum - Sentenská, Lenka; Pekár, Stano; Uhl, Gabriele (Die Naturwissenschaften, 2018)
In order to avoid sperm competition, males of many taxa apply physical barriers, so-called mating plugs, into female genitalia. Females may control which males deposit a plug through pre-copulatory mate choice or by influencing plug efficacy to avoid costs imposed by plugging. However, subsequent suitors might remove the plugs. We investigated behavioural and morphological aspects of plug deposition and removal in a promiscuous spider, Philodromus cespitum (Philodromidae). We performed mating trials to investigate factors affecting plugging. To identify the plug origin, we conducted a morphological analysis using 3D X-ray microtomography and histology of the male copulatory organ and the female genital tract. In P. cespitum, the plug material is produced in the male genital bulb and transferred to the female together with sperm. The copulation is brief and terminated by the female. After mating, plugging material was found in the genital atrium of all females, covering it to a varying degree (10-100%). The extent of coverage was associated with the duration of movements of male copulatory organ connected with sperm transfer (i.e. full haematodochal expansions) and with the number of taps a male delivered with his legs to the female during courtship. Males larger than the female performed more tapping movements. Mating trials with plugged females revealed that males could remove plugs partly or entirely. Removal success increased with increasing foreleg length ratio between the male who removed the plug and the one who deposited it. We discuss our results in the light of the potential female control of plug deposition and removal.
Keywords: rozmnožování; Reproduction; Courtship; X-ray microscopy; Sexual Behavior, Animal; Male; Genital morphology; Animals; Sperm competition; Female; mužské pohlaví; ženské pohlaví; pavouci; Polyandry; Female mate choice; sexuální chování zvířat; zvířata; Spiders